The Effectiveness of Busy Book Media on Fine Motor Skills of 4-5 Year Old Children at KB Ainul Husna, Padang Panjang City - Yulia Purnamasari; Yuliani Eka Putri; Asla De Vega (Suluah Pasaman, 2026)
This research is motivated by the importance of using interesting and interactive educational media to support the development of early childhood skills, especially fine motor skills. Busy Book is a learning media designed to create a fun learning atmosphere and increase children's motivation and enthusiasm in classroom activities. The purpose of this study was to test the effectiveness of using Busy Book on improving children's fine motor skills at KB Ainul Husna, Padang Panjang City. The study used a quantitative approach with a quasi-experimental design. The study population included 45 children, with a purposive sample of 24 children from grades B1 and B2. Data analysis was carried out through prerequisite tests, independent sample t-tests, and effect size calculations using SPSS 26.0 for Windows. The results showed that the experimental group using Busy Book experienced an increase in average scores from 32.08 to 45.33, while the control group using the collage method increased from 32.58 to 40.58. The t-test produced a significance value of 0.000, indicating a significant difference between the two groups. The effect size value of d = 2.22 indicates a very strong effect. Thus, the use of Busy Book media has proven effective in improving the fine motor skills of early childhood children at KB Ainul Husna in Padang Panjang City. The results of this study imply that Busy Book can be used as an effective and engaging alternative learning medium to stimulate fine motor skills in early childhood education activities.